2000
DOI: 10.1109/58.818773
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the bulk, C-axis electromechanical coupling constant as a function of AlN film quality

Abstract: Piezoelectric thin film AlN has great potential for on-chip devices such as thin-film resonator (TFR)-based bandpass filters. The AlN electromechanical coupling constant, K(2), is an important material parameter that determines the maximum possible bandwidth for bandpass filters. Using a previously published extraction technique, the bulk c-axis electromechanical coupling constant was measured as a function of the AlN X-ray diffraction rocking curve [full width at half maximum (FWHM)]. For FWHM values of less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…The full width of half maximum (FWHM) of the rocking curve was measured by X-ray diffraction (XRD) to assess, quantitatively, the preferred (002) orientation as shown in Figure 2. Generally, a (002)-oriented AlN film with the FWHM less than 4˝is the precondition of good piezoelectric property [14]. The FWHM of the rocking curve around (002) orientation for the AlN sample was about 1.9˝, which meant the AlN thin film has a good piezoelectric property.…”
Section: Methodsmentioning
confidence: 94%
“…The full width of half maximum (FWHM) of the rocking curve was measured by X-ray diffraction (XRD) to assess, quantitatively, the preferred (002) orientation as shown in Figure 2. Generally, a (002)-oriented AlN film with the FWHM less than 4˝is the precondition of good piezoelectric property [14]. The FWHM of the rocking curve around (002) orientation for the AlN sample was about 1.9˝, which meant the AlN thin film has a good piezoelectric property.…”
Section: Methodsmentioning
confidence: 94%
“…Thus, K 2 is large, but v is limited by the smaller velocity value of the A1N overlayer. In addition to the intrinsic limitations imposed by the dispersion of the material system, the crystal quality and orientation of the sputtered A1N thin films, and thus their piezoelectricity, are limited by the film thickness [7], [8]. Moreover, the insulating character of A1N makes the e-beam patterning of the submicrometer IDTs more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The AlN films were sputtered at various conditionssubstrate temperature from room temperature to 300°C, N 2 /Ar gas ratio of 9 to 1, pressure of 1 to 6mTorr, and power of 1 to 4kW -to obtain optimized films' properties. X-ray diffraction (XRD) rocking curve analysis was used to characterize the sputtered films since it has been shown that there is a correlation between the full width at half maximum (FWHM) of the XRD rocking curve and piezoelectric properties (Naik et al, 2000;Liaw & Hickernell, 1995). Fig.…”
Section: Piezoelectric Aln Filmsmentioning
confidence: 99%
“…Based on the initial sensor design (Gerfers et al, 2006), this chapter introduces the technique of stress concentration to improve the overall accelerometer SNR . In the first section, the deposition of highly c-axis oriented AlN films is described, since optimal piezoelectric and crystal properties of AlN films are essential for devices' performance (Ruby & Merchant, 1994;Naik et al, 2000). Furthermore, Section 2 discusses processing details and experimental results of the sputtered piezoelectric AlN films.…”
Section: Introductionmentioning
confidence: 99%